THE EFFECTS OF THE HOSPITAL NETWORK SYSTEM OF CARDIAC EMERGENCY CARE ON PRE-HOSPITAL TIME DELAYS IN PATIENTS WITH ACUTE MYOCARDIAL INFARCTION - KURODA, Sigeomi; TOKITA, Yukichi; YAMASHINA, Ikuko; UEMURA, Ryota; TANABE, Jun; OGAWA, Akiho; TAKAYAMA, Hideo; KOJIMA, Syunichi; YOKOYAMA, Hiroyuki (Japanese Journal of National Medical Services, 2003)
It is clear that use of reperf usion therapies has let to impressive reductions in mortality from acute myocardial infarction (AMI). However, only 30 to 40% of patients with AMI received these therapies, because many patients do not arrive on the hospital in time to benefit with them. We established the hospital network system of cardiac emergency care by five hospitals to reduce the pre-hospital time delay in patients with AMI. In this study, we tested the effects of the hospital network system of cardiac emergency care on pre-hospital time delays in patients admitted to our hospital with AMI before and after starting on hospital network system. After starting on hospital network system, the percentage of patients with AMI directly transferred to the hospital by ambulance was significantly increased from 10% to 34%. However, the median time from onset of AMI to hospital arrive was not changed from 3.1 hour to 3.5 hour. The most frequent reason of the pre-hospital delay was the patient's decision delay such as they did not realized their chest pain as being life-threatening. In a future work, we have to address to educate the patients with coronary risk factors about symptoms of AMI and the need to get the hospital quickly.